Antimicrobial Test of 1-(2.5-Dihydroxi Phenyl)-(3-Pyridine-2-Il) -Propanone Compound in Enterococcus Faecalis and Escherichia Coli Bacteria Using a Well Diffusion Method - Andy Eko Wibowo; Rivaldy Rifai Hatala; Awalludin M Edang (Universitas Muhammadiyah Yogyakarta, 2021)
1-(2.5-dihydroxy phenyl)-(3-pyridine-2-il)-propenone compound is a compound synthesized by reacting the pyridine-2-carbaldehyde and 2.5-dihydroxyacetophenone compound without solvent with K2CO3 (Potassium Carbonate) catalyst in the microwave. The 1-(2.5-dihydroxy phenyl)-(3-pyridine-2-il)-propenone compound is a chalcone derivative compound substituted by two hydroxy groups on ring A and has 2-pyridyl groups on ring B. Chalcone is a secondary metabolite compound from the flavonoid group, which has several activities as anti-platelet, anti-bacterial, immunomodulator, anti-hyperglycemic, and anti-inflammatory. This study aims to determine the antibacterial effect of 1-(2.5-dihydroxifenil)-(3-pyridine-2-il)-propenone compound against Enterococcus faecalis and Escherichia coli bacteria. This study used TLC (Thin Layer Chromatography) and Melting Point Test to analyze the purity of 1-(2.5-dihydroxy phenyl)-(3-pyridine-2-il)-propenone compound. Meanwhile, the test for antibacterial activity used a well diffusion method. Concentration variation for 1-(2.5-dihydroxifenyl)-(3-pyridine-2-il)-propenone compound as antibacterial in Escherichia coli were 0.25 mg/100 μl, 0.5 mg/200 μl, and 0.75 mg/300 μl. Meanwhile, the concentration variation for Enterococcus faecalis bacteria was 5%, 2.5%, 1.25% and was replicated three times. The results of the compound purity test using the melting point test and Thin Layer Chromatography (TCL) showed that the 1-(2.5-dihydroxy phenyl)-(3-pyridine-2-il)-propenone compound was pure. The results of the antibacterial activity test for 1-(2.5-dihydroxiphenyl)-(3-pyridine-2-il)-propenone compound showed no zone of inhibition at each test concentration. In conclusion, the 1-(2.5-dihydroxifenyl)-(3-pyridine-2-il)-propenone compound did not have an antibacterial effect on Enterococcus faecalis and Escherichia coli bacteria.